Root Morphology and Physiology in Relation to the Yield Formation of Rice - Jian-chang YANG; Hao ZHANG; Jian-hua ZHANG (Journal of Integrative Agriculture, 2012)
Root system is a vital part of plant and regulates many aspects of shoot growth and development. This paper reviews how some traits of root morphology and physiology are related to the formation of grain yield in rice (Oryza sativa L.). Higher root biomass, root oxidation activity, and cytokinin contents in roots are required for achieving more panicle number, more spikelets per panicle, greater grain-filling percentage, and higher grain yield. However, these root traits are not linearly correlated with yield components. When these traits reach very high levels, grain filling and grain yield are not necessarily enhanced. High numbers of mitochondria, Golgi bodies, and amyloplasts in root tip cells benefit root and shoot growth and yield formation. Proper crop management, such as an alternate wetting and moderate soil drying irrigation, can significantly improve ultra-structure of root tip cells, increase root length density and concentration of cytokinins in root bleedings, and consequently, increase grain-filling percentage, grain yield, and water use efficiency. Further studies are needed to investigate the mechanism underlying root-shoot and root-soil interactions for high grain yield, the roles of root-sourced hormones in regulating crop growth and development and the effects of soil moisture and nutrient management on the root architecture and physiology.